2020
DOI: 10.1111/ger.12468
|View full text |Cite
|
Sign up to set email alerts
|

Rate of oral frailty and oral hypofunction in rural community‐dwelling older Japanese individuals

Abstract: Objective: To clarify the rate of oral frailty and oral hypofunction in rural communitydwelling older adults in Japan. Background: Recently, the oral function of Japanese older adults has been evaluated multilaterally based on two concepts: oral frailty and oral hypofunction. Oral frailty is defined as a decrease in the oral function accompanied by a decrease in mental and physical functions. Oral hypofunction is a disease where the oral function is comprehensively decreased. However, their rates have not yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 39 publications
8
71
7
Order By: Relevance
“…Patients in the Low group had larger number of untreated teeth possibly because they did not visit the dentist regularly. As reported in men, a close relationship was evident between the number of remaining teeth and masticatory function in the women of this study [41,42]. Therefore, when the groups were compared, we found that the target population had pathologies consistent with previous reports, which may increase the validity of this study.…”
Section: Discussionsupporting
confidence: 88%
“…Patients in the Low group had larger number of untreated teeth possibly because they did not visit the dentist regularly. As reported in men, a close relationship was evident between the number of remaining teeth and masticatory function in the women of this study [41,42]. Therefore, when the groups were compared, we found that the target population had pathologies consistent with previous reports, which may increase the validity of this study.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, the prevalence of oral hypofunction based on diagnostic criteria published by the JSG was 50.5% overall, 40.3% among men, and 54.9% among women. Previous reports have indicated that the prevalence of oral hypofunction among older adults living in different regions of Japan is 43.6–61.6% overall, 39.0–62.6% among men, and 46.9–63.1% among women [ 10 , 39 , 40 , 41 ]. The prevalence of oral hypofunction in our study was within the range previously reported among community-dwelling older adults.…”
Section: Discussionmentioning
confidence: 99%
“…However, little information is known on the current state of oral hypofunction in independent older people based on these evaluation criteria. 14 The association of oral hypofunction or a combination of decreased oral functions with frailty is also not clear. Therefore, it is important to investigate the current status of oral hypofunction in older people and to assess the association between oral function and frailty.…”
Section: Introductionmentioning
confidence: 99%
“…Examinations to determine oral hypofunction were added as clinical test items in the Japanese public health insurance system during the fiscal year 2018. However, little information is known on the current state of oral hypofunction in independent older people based on these evaluation criteria 14 . The association of oral hypofunction or a combination of decreased oral functions with frailty is also not clear.…”
Section: Introductionmentioning
confidence: 99%